Acid–base properties of an antivirally active acyclic nucleoside phosphonate: (S)-9-[3-hydroxy-2-(phosphonomethoxy)propyl]adenine (HPMPA). (16th March 2022) - Blindauer, Claudia A.; Holý, Antonín; Sigel, Astrid; Operschall, Bert P.; Griesser, Rolf; Sigel, Helmut
Abstract : Protonation equilibria for the parent compound of three highly potent antivirals have been studied by 1 H NMR spectroscopy. Abstract : HPMPA is an acyclic nucleoside phosphonate analogue of AMP which displays antiviral properties. Therefore, its acid–base behavior as well as that of related compounds like PMEA, 9-[2-(phosphonomethoxy)ethyl]adenine, are for many reasons ( e.g., binding to enzymes, coordination of metal ions) of general interest. HPMPA can accept two protons at the phosphonate and two more at the adenine residue, but not all acidity constants are accessible by potentiometric pH titrations. Therefore, we measured the chemical shifts of the nine non-exchangeable HPMPA protons by 1 H NMR in D2 O in dependence on pD in the range from 1 to 12. The corresponding results allowed identifying the protonation sites and, transferred to aqueous solution, they gave also the acidity constants. The most basic site is the phosphonate group followed by N1 of adenine. The p K a values increase from ca. −0.27 [–N7(H) + ] via 1.27 [–PO(OH)2 ] and 4.23 [–N1(H) + ] to 6.86 [–PO(OH) − ]. In the fully protonated species charge repulsion exists between N1(H) + and N7(H) + ; therefore, the affinity of N7 for H + is not correctly reflected by the measured acidity constant ( ca. −0.27). Needed is the intrinsic micro acidity constant which reflects the H + affinity of N7 under conditions where N1 is unprotonated; we abbreviate this species as + H·N7(HPMPA)N1. The corresponding microconstant is estimated to be p k N7–N1H·N7–N1 3.5; the minor species + H·N7(HPMPA)N1 occurs with an estimated formation degree between about 5 to 20%. The basicity of the adenine nitrogens decreases in the order N1 > N7 > N3.